2008
DOI: 10.1016/j.febslet.2008.05.047
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Hsp110, Sse1p, exhibits high‐affinity peptide binding

Abstract: Hsp110s are divergent relatives of Hsp70 chaperones that hydrolyze ATP. Hsp110s serve as Hsp70 nucleotide exchange factors and act directly to maintain polypeptide solubility. To date, the impact of peptide binding on Hsp110 ATPase activity is unknown and an Hsp110/peptide affinity has not been measured. We now report on a peptide that binds to the yeast Hsp110, Sse1p, with a K D of $2 nM. Surprisingly, the binding of this peptide fails to stimulate Sse1p ATP hydrolysis. Moreover, an Hsp70-binding peptide is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 34 publications
6
53
0
1
Order By: Relevance
“…22,23,[58][59][60] Among HSPs, HSP110 exhibits higher binding affinity with proteins when compared to the HSP70s family. 39,40,47,48,56,61 Consequently, a potent immune response was generated by the addition of HSP110, as observed in our studies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…22,23,[58][59][60] Among HSPs, HSP110 exhibits higher binding affinity with proteins when compared to the HSP70s family. 39,40,47,48,56,61 Consequently, a potent immune response was generated by the addition of HSP110, as observed in our studies.…”
Section: Discussionsupporting
confidence: 62%
“…29,[37][38][39] In contrast to HSP70, the peptide-specific chaperon properties of HSP110 remain largely uncharacterized. 40 Goeckeler et al reported that yeast HSP110 exhibited high-affinity binding in vitro with peptide derived from the precursor of chicken mitochondrial aspartate aminotransferase, suggesting Hsp110 may be highly effective in anti-cancer peptide-based vaccines. 40 In this study, we combined the extensively studied HPV16 E7 [49][50][51][52][53][54][55][56][57] (RAHYNIVTF) CTL epitope [41][42][43][44][45] with the high-affinity peptide binding chaperone property of mouse HSP110 to improve antigen peptide presentation, generate HPV16 E7 [49][50][51][52][53][54][55][56][57] specific CTL response and enhance the anti-tumor ability in a cervical cancer murine model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ER, where BiP is the only ER Hsp70 family member, this is a possibility, but in the cytosol, which contains multiple constitutive and inducible Hsp70s and in some cases also possesses several large Hsp70s, this possibility is less appealing. Alternatively, it is possible that Grp170 and BiP bind to different sites on the same substrates or do not have completely overlapping substrates, as suggested by in vitro studies with large Hsp70s (42,43,47). Finally, the binding of Grp170 to proteins might signal a different fate for the substrate than when it is associated with BiP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Fes1, Hsp110 is a chaperone that recently has been shown to directly bind hydrophobic peptides (41)(42)(43). Thus, direct binding of hydrophobic patches might help to maintain the misfolded protein soluble, help the protein to fold, and shield it from interactions with the ubiquitylation machinery.…”
Section: Discussionmentioning
confidence: 99%